ANXIETY, STRESS AT WORK, AND EMPLOYEE TRUST: A STUDY WITH BRAZILIAN CIVIL SERVANTS - Menegazzi, Raquel Boff; Lopes, Luis Felipe Dias; Silva, Deoclécio Junior Cardoso da; Moreira, Martiele Gonçalves; Amaral, Luciano; Lopes, Fillipe Grando (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2023)
Objective: This study aimed to analyze the degree of anxiety, stress at work, and employee trust, as well as whether anxiety is a moderator in the relationship between stress at work and employee trust dimensions in Brazilian civil servants during the COVID-19 pandemic. Methodology: A quantitative study was conducted between July and August 2021, in which answers were obtained from 375 Brazilian civil servants. The results were analyzed using descriptive statistics techniques and partial least squares structural equation modeling to verify the relationships between the constructs. Results: Our findings revealed direct relationships between the constructs of stress and anxiety, direct relationships between anxiety and trust, and indirect relationships between stress and trust. Implications: This study presents managerial and theoretical contributions by bringing relevant reflections on the mental health of Brazilian civil servants during the COVID-19 pandemic.